Abdominal aorta calcification predicts cardiovascular but not non-cardiovascular outcome in patients receiving peritoneal dialysis: A prospective cohort study. Issue 37 (11th September 2020) - Tsai, Cheng-Hsuan; Lin, Lian-Yu; Lin, Yen-Hung; Tsai, I-Jung; Huang, Jenq-Wen
Abstract : Abstract: Abdominal aorta calcification (AAC) is associated with worse clinical outcomes in dialysis patients. However, the long-term prognostic values of AAC to cardiovascular (CV) and non-CV mortality in patients starting peritoneal dialysis (PD) remain unknown. This study is aimed to the analyze the predictive power of AAC to CV and non-CV mortality in PD patients. We prospectively enrolled 123 patients undergoing PD. All patients received quantitative analysis of AAC via abdominal computer tomography at enrollment. The AAC ratio was measured by the area of the whole aorta affected by aortic calcification above the iliac bifurcation. The CV mortality and non-CV mortality during the follow-up period were investigated using the Cox proportional hazard model and time-dependent receiver operating characteristic (ROC) analysis. After median 6.8 (interquartile range, 3.6–9.2) years of follow-up, there were 18 CV mortality, 24 non-CV mortality and 42 total mortality. The age and AAC ratio were significantly higher in CV mortality group compared with others without CV mortality. In time-dependent ROC analysis, AAC had excellent predictive power of CV mortality (AUC:0.787) but not non-CV mortality (AUC:0.537). The best cutoff value of AAC ratio to predict CV mortality was 39%. In addition, AAC was not associated with non-CV mortality but remained to be a significantly predictor of CV mortality after adjusted with clinical covariates in different Cox proportional hazard models. AAC has excellent prognostic value of CV mortality but is unable to predict non-CV morality in patients undergoing PD.